Correction to: Muscle and tendon morphology alterations in children and adolescents with mild forms of spastic cerebral palsy - Annika Kruse; Christian Schranz; Markus Tilp; Martin Svehlik (BMC, 2018)
Following publication of the original article [1], the author requested for an acknowledgement to retrospectively be added to the 'Acknowledgements' section of the article [1].